2019
DOI: 10.1016/j.nuclphysb.2019.114636
|View full text |Cite
|
Sign up to set email alerts
|

Simplest radiative Dirac neutrino mass models

Abstract: If neutrinos are Dirac particles, their right-handed partners must be present in the theory. Once introduced in the Standard Model (SM), the difference between the baryon number B and the lepton number L can be promoted to a local U (1) B−L symmetry since the corresponding gauge anomalies can be canceled by the right-handed neutrinos. Furthermore, the extremely small neutrino mass can be explained naturally if it is originated from the quantum correction. In this work, we propose simplest models of radiative D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 114 publications
(162 reference statements)
0
27
0
Order By: Relevance
“…However, tree-level Dirac type-I seesaw with proper choices for the U(1) B−L charges have been shown to be consistent without require any extra ad-hoc discrete symmetries [17]. In recent works, it has been shown that even for one-loop Dirac neutrino masses, it is possible to have U(1) B−L as the only extra symmetry beyond the SM [24][25][26] 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tree-level Dirac type-I seesaw with proper choices for the U(1) B−L charges have been shown to be consistent without require any extra ad-hoc discrete symmetries [17]. In recent works, it has been shown that even for one-loop Dirac neutrino masses, it is possible to have U(1) B−L as the only extra symmetry beyond the SM [24][25][26] 1 .…”
Section: Introductionmentioning
confidence: 99%
“…For extensions with only extra scalars, minimal solutions have been found with two and three loops[26].…”
mentioning
confidence: 99%
“…Whereas a systematic classification of Majorana neutrino mass mechanisms and identifying minimal models are extensively discussed in the literature [74][75][76][77][78][79][80][81][82][83], similar analysis for the case of Dirac neutrinos are still lacking. Along this direction, some recent attempts are taken: a systematic classification of tree-level and one-loop mass mechanisms at d = 4 [84], d = 5 [85,86], d = 6 [87,88], two-loop mass models at d = 4 [84,89], selecting minimal models at one-loop [49] and identifying simplest models at one-loop, two-loop and three-loop [53] are considered.…”
Section: Higgsmentioning
confidence: 99%
“…Within this framework, by employing the U (1) R symmetry we construct a tree-level Dirac seesaw model [27] and two models where neutrino mass appears at the one-loop level. One of these loop models presented in this work is the most minimal model of radiative Dirac neutrino mass [28] and the second model uses the scotogenic mechanism [29] that links two seemingly uncorrelated phenomena: neutrino mass with Dark Matter (DM). As we will discuss, the stability of the DM in the latter scenario is a consequence of a residual Z 2 discrete symmetry that emerges from the spontaneous breaking of the U (1) R gauge symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also study the associated charged lepton flavor violating processes, dark matter phenomenology and cosmological constraints of these models. * metry [30] for generating the Dirac neutrino mass [28,[31][32][33][34][35]. Both of the two possibilities are attractive and can be regarded as the minimal gauge extensions of the SM.…”
mentioning
confidence: 99%